PENGGUNAAN TEPUNG DAUN ECENG GONDOK (Eichornia crassipes) PADA RANSUM KOMERSIL TERHADAP PENAMPILAN JANGKRIK (Gryllidae) - Siti Dharmawati; Neni Widaningsih; Supirah Supirah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The purpose of this study was to determine the effect of mixing commercial ration with water hyacinth leaf meal on the performance of crickets.This study used a completely randomized design (CRD) with five treatments and four replications ie without giving hyacinth leaf powder and water hyacinth leaf powder administration of 5%, 10%, 15% and 20%. The data were analyzed using Homogenetas Test (Bartlett), F test (analysis of variance) and the region continued Duncan's Multiple Test (DMRT).The results showed that the mixing of water hyacinth leaf meal in the ration significantly affect weight gain and final body weight crickets but no significant effect on feed intake, feed conversion, body length and mortality crickets.